Effect of Prenatal Gentle Yoga on Low Back Pain Among Pregnant Women: A Quasi-Experimental Study - Dwi Nur Octaviani Katili; Sri Nur Ain Laliyo; Yuliandary Yunus; Efri Leny Rauf (PT.Mantaya Idea Batara, 2025)
Introduction: Low back pain (LBP) during pregnancy can interfere with physical activity, sleep patterns, and quality of life. One safe and effective therapy to relieve it is prenatal gentle yoga. The purpose of this study was to determine the effect of prenatal gentle yoga on the level of LBP in pregnant women at Hulonthalangi Health Center. The research design used quasi-experiment with pretest-posttest control group. A total of 24 pregnant women were divided into two groups, those are intervention (prenatal gentle yoga) and control (educational leaflet). The prenatal gentle yoga intervention was carried out over four sessions, with a frequency of twice a week, and each session lasted for 30 to 45 minutes.Test results of independent t-test showed an average difference in pain of -2.83 points with a p-value of 0.000 (p<0.05), which means there was a significant decrease in pain in the intervention group. Around 83.3% respondents in the intervention group experienced a decrease in pain from moderate and severe pain to mild and no pain, while the control group only had 33.3%. This study shows that prenatal gentle yoga is significantly effective in reducing Low back pain (LBP) in pregnant women.